PENGARUH PEMBERIAN RANSUM YANG BERBEDA TERHADAP KUALITAS PUTIH TELUR - Andi Suarda (Fakultas Sains dan Teknologi Universitas Islam Negeri Alauddin Makassar, 2015)
This research aimed to get an idea of the extent to which different rations pemberian influence on the quality of the egg white. Material used in this research is the production phase of the laying hens numbered 48 animals, aged nine months, and the strains of